Analisis Kesulitan Mahasiswa Matematika dalam Belajar Teori Grup di Masa Pandemi Covid-19 - Diyah Hoiriyah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This article aims to analyze the difficulties in learning mathematics of students in the Tadris/Mathematics Education Study Program during the online learning process in the Group Theory course during the Covid-19 Pandemic. This type of research is descriptive qualitative research. The research subjects were students of the fifth semester of Tadris/Mathematical Education, Faculty of Tarbiyah and Teacher Training at IAIN Padangsidimpuan who took the Group Theory course. The research data was taken from a questionnaire on learning difficulties in mathematics which was distributed to students. The results of the data analysis showed that students experienced some difficulties in learning mathematics during the online learning process. The learning difficulties faced by these students are; 1) 88.86% of the difficulties faced by students in terms of technical problems affecting the wifi signal/network; 2) 75.43% of the difficulties faced by students in terms of students' inability to understand Group Theory material through online learning both in terms of defining, giving examples to providing proof of Group Theorem and solving problems in Group Theory; 3) then 78.04% of interactions during the online learning process that are less focused; and 4) 74.09% of students experience difficulties in terms of assignments and teaching materials in online learning.